2016
DOI: 10.22146/ijg.12488
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of Traffic-Related Air Pollution Using GIS Techniques in Ijebu-Ode, Nigeria

Abstract: Spatial and temporal characteristics of traffic related air pollutants (CO, NO, NO 2 and SO 2 ) in Ijebu-ode, Nigeria were determined using replicate portable gas detectors (Land Duo Multi Gas Monitor) at selected road junctions, motor garages and markets. Mapping of different concentration of air pollutants was carried out using kriging type of interpolation method in GIS environment. Concentration of CO ranges from 4.8 ppm at Erinlu/Molipa Roundabout to 137ppm on Sagamu/Ore Expressway. Concentrations of NO 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 28 publications
2
12
2
Order By: Relevance
“…The finding reveals that the AQI for CO in Kaduna Metropolis ranges from good to hazardous, this agree with the findings of Saniei et al (2016) on Air quality classifica-tion and its temporal trend in Tehran, Iran, and Attah (2015). The finding disagrees with the submission of Chizoruo et al (2017) on the ambient air quality assessment of Orlu, Southeastern, Nigeria, and Adedeji et al (2016) whose finding shows only unhealthy and very unhealthy AQI. The result reveals that 21.21% of the sample sites air quality base on USEPA and WHO standard are good, in as the NESREA standard shows that 33.33% are good, the good sites are fairly distributed in both the north and southern part of the study area (Table 2).…”
Section: Raining Season Aqicontrasting
confidence: 91%
See 2 more Smart Citations
“…The finding reveals that the AQI for CO in Kaduna Metropolis ranges from good to hazardous, this agree with the findings of Saniei et al (2016) on Air quality classifica-tion and its temporal trend in Tehran, Iran, and Attah (2015). The finding disagrees with the submission of Chizoruo et al (2017) on the ambient air quality assessment of Orlu, Southeastern, Nigeria, and Adedeji et al (2016) whose finding shows only unhealthy and very unhealthy AQI. The result reveals that 21.21% of the sample sites air quality base on USEPA and WHO standard are good, in as the NESREA standard shows that 33.33% are good, the good sites are fairly distributed in both the north and southern part of the study area (Table 2).…”
Section: Raining Season Aqicontrasting
confidence: 91%
“…This result disagrees with the submission of Attah (2015) who reported that the AQI of SO 2 is good in all the traffic sites in Kaduna metropolis, and also the submission of Chizoruo et al (2017) who reported the AQI of SO 2 to be only very unhealthy and hazardous. However, agrees with the findings of Adedeji et al (2016). The finding equally reveals that 27.27% of the sites AQI is good base on USEPA standard and NESREA standard shows an increase 36.36% of the locations.…”
Section: Sosupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, the spatial air pollutants mapping clearly can provide significant contribution to mark dispersion of air borne pollutants. (Adedeji et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Air pollution is one of the main contributors to environmental (global warming, transboundary transport of smoke, acid rain, ozone layer depletion) and health (breathing and cardiovascular disorders, exacerbation of asthma, impaired lung capacity and premature death) [6][7][8] issues. Given the adverse environmental and health effects of air pollution, there is a need for assessment and continuous monitoring of air quality for environmental sustainability.…”
Section: Introductionmentioning
confidence: 99%